Get off my brain : a survival guide for lazy students - McCutcheon, Randall, 1949- (Hawker Brownlow Education, 1992)
An illustrated guide to ways of improving study habits with suggestions for writing creative papers, making speeches, doing research, getting good grades, and time management.